Systematic Review on Treating Knee Osteoarthritis with Bushen Zhuangjin Decoction - Suixin HUANG; Jie LIN; Xihai LI (康复学报)
Objective:To evaluate the curative effect of Bushen Zhuangjin decoction on treating knee osteoarthritis.Methods:Randomized control trials (RCTs) on treating knee osteoarthritis with Bushen Zhuangjin decoction in database of CNKI, CQVIP, Wan Fang, Pubmed before October 31, 2016 were retrieved. RevMan 5.3 was applied for qualitative analysis of the data survey and meta-analysis.Results:A total of five studies were included in this study. The results of Meta analysis showed that the Bushen Zhuangjin decoction treatment group was better than that of the control group or the conventional western medicine treatment group in releasing arthritis symptom.Conclusion:Bushen Zhuangjin decoction should provide an effective therapy strategy for knee oateoarthritis, which needs to be confirmed with high quality clinic investigations.